Designing Load-Bearing Bio-Inspired Materials for Simultaneous Static Properties and Dynamic Damping: Multi-Objective Optimization for Micro-Structure - Bo Dong; Yunfei Jia; Wei Wang (Chinese Journal of Mechanical Engineering)
Abstract Biological load-bearing materials, like the nacre in shells, have a unique staggered structure that supports their superior mechanical properties. Engineers have been encouraged to imitate it to create load-bearing bio-inspired materials which have excellent properties not present in conventional composites. To create such materials with desirable mechanical properties, the optimum structural parameters combination must be selected. Moreover, the optimal design of bio-inspired composites needs to take into account the trade-offs between various mechanical properties. In this paper, multi-objective optimization models were developed using structural parameters as design variables and mechanical properties as optimization objectives, including stiffness, strength, toughness, and dynamic damping. Using the NSGA-II optimization algorithm, a set of optimal solutions were solved. Additionally, three different structures in natural nacre were introduced in order to utilize the better structure when design bio-inspired materials. The range of optimal solutions that obtained using results from previous research were examined and explained why this collection of optimal solution ranges is better. Also, optimal solutions were compared with the structural features and mechanical properties of real nacre and artificial biomimetic composites to validate our models. Finally, the optimum design strategies can be obtained for nacre-like composites. Our research methodically proposes an optimization method for achieving load-bearing bio-inspired materials with excellent properties and creates a set of optimal solutions from which designers can select the one that best suits their preferences, allowing the fabricated materials to demonstrate preferred performance.